2021
DOI: 10.3390/plants10071432
|View full text |Cite
|
Sign up to set email alerts
|

Differential Responses of Antioxidative System during the Interaction of Soursop Fruits (Annona muricata L.) and Nectria haematococca at Postharvest Storage

Abstract: Soursop fruit (Annona muricata L.) production is diminished by the attack of pathogens such as Nectria haematococca. However, the fruit–pathogen interaction at the biochemical and molecular levels is still unknown. The objective of this study was to analyze the response of the soursop fruit to the presence of N. haematococca during postharvest storage. Soursop fruits were inoculated with the pathogen and total phenolic compounds, antioxidant capacity by Ferric reducing/antioxidant power (FRAP), 2,2′-azinobis-(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…22,23 The production of phytoalexins, one of the phenolic compounds toxic to many pathogens, is a systemic early response to presence of fungus and bacteria. 24 On the other hand, the non-existence of difference in TP content in Kurtovska kapia genotypes can suggest that this antioxidant response is genotype dependent, which is in agreement with Ribes-Moya et al 25 Antioxidant capacity measured by DPPH, NBT and TRC showed variability depending on genotype and treatment (Fig. 1).…”
Section: Accepted Manuscriptsupporting
confidence: 85%
See 1 more Smart Citation
“…22,23 The production of phytoalexins, one of the phenolic compounds toxic to many pathogens, is a systemic early response to presence of fungus and bacteria. 24 On the other hand, the non-existence of difference in TP content in Kurtovska kapia genotypes can suggest that this antioxidant response is genotype dependent, which is in agreement with Ribes-Moya et al 25 Antioxidant capacity measured by DPPH, NBT and TRC showed variability depending on genotype and treatment (Fig. 1).…”
Section: Accepted Manuscriptsupporting
confidence: 85%
“…In Kurtovska kapia, all antioxidant tests showed decrease in antioxidant activity in infected fruits. Rubio-Melgarejo et al 24 suggested that pathogen may manipulate the defense response, modifying the signalling network and cause decrease in the antioxidant activity. Variations in the results of antioxidant activity may be related to the different…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The antioxidant activities for A. acida peels was better than those of tangerine ( Citrus reticulata ) and pineapple ( Ananas comosus ) peels, which evidenced IC 50 values of 97.3 and 209.6 µg/mL, respectively (Campos et al., 2020; Zhang et al., 2006). Additionally, the ABTS method evidenced better antioxidant activity in the fruit pulp of A. acida as compared to the fruits of “mangaba” (IC 50 value of 394.5 g/mL) as well as karonda ( Carissa carandas ) and soursop ( Annona muricata ) which had IC 50 values of 101.77 and 160.0 g/mL, respectively (Rubio‐Melgarejo et al., 2021; Sarkar et al., 2018; Sergio et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Hernández-Guerrero et al [37] isolated and identified the pathogen N. haematococca in soursop fruits using morphological and molecular tools. Indeed, Rubio-Melgarejo et al [38] showed that N. haematococca attacks soursop fruits and stimulates the antioxidative system during ripening. Fusarium chlamydosporum, F. wollenwebe, and F. reinking species have also been identified as soursop pathogens [39].…”
Section: Discussionmentioning
confidence: 99%